Media, migrants and the pandemic in India : a reader - Bhushan, Bharat (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"The national lockdown to contain the Covid-19 pandemic in India resulted in the loss of work and displacement of thousands of urban migrant workers. This book records the arduous journey home for many of these workers and analyses the grave effects the pandemic has had on jobs, livelihoods, and the health of urban migrant workers. A rich compilation of deep analytical articles by journalists, academics, lawyers and social activists, this book explores various facets of the crisis as it unfolded. It examines welfare policies of state and central governments and discusses the role of the judiciary and the public policy response to unemployment, health risks and mass migration of workers. It also offers readers a better understanding of the complexities of the migrant crisis, how it unfolded and how it was addressed by the media. This timely and prescient book will be of great interest to the general reader as well as researchers and students of media studies, journalism, sociology, law, public policy, labour and economics, welfare economics, gender studies, and development studies"--
Faceless and dispossessed : India's circular migrants in the times of COVID-19 / Priya Deshingkar -- How many casual workers in the cities have sought to go home? / Nomaan Majid -- Migration in India and the impact of the lockdown on migrants / Madhunika Iyer -- Labour commissioner puts total number of migrant workers at 26 Lakh, says 10% in relief camps / Gaurav Vivek Bhatnagar -- Why India's legal and labour system needs to be reconfigured to really help migrant workers / Satvik Varma -- Covid-19 crisis exposes India's neglect of informal workers / Jenny Sulfath and Balu Sunilraj -- National Commission for Women : advisory to address needs of internal women migrants in India during COVID-19 Lockdown -- How the Supreme Court and the High Courts have dealt with worst migrant crisis faced by the nation / Ejaz Maqbool, Akriti Chaubey and Mohammad Isa Hakim -- Migrants workers, the lockdown and the judiciary / Harsh Mander -- Justice Madan Lokur : Supreme Court deserves an 'F' grade for its handling of migrants / Madan B. Lokur -- Women workers in labour codes / Indrani Mazumdar and Neetha N Pillai -- No train. No bus. Just a rickety cycle to cover 600 km - on an empty stomach / Supriya Sharma -- Nightmare on Shramik Specials / V Sridhar -- Not just the aurangabad accident, 383 people have died due to the punitive lockdown / Kabir Agarwal -- As Manipuri workers return home from goa, what does the future hold for baby Emmanuel Quarentino? / Nandita Haksar -- Covid-19 : Odia women migrants suffer mental stress, feel nobody heeds to their plight / Rakhi Ghosh -- Why don't we see the women? The untold story of Covid-19 migration / Ipsita Sapra -- Social distancing and sex workers in India / Priyanka Tripathi and Chhandita Das -- Can the State let employers walk away from lockdown wages? / Bharat Bhushan -- Hunger grows as India's lockdown kills jobs / Rahul Lahoti, Amit Basole, Rosa Abraham, Surbhi Kesar and Paaritosh Nath -- COVID-19 : intra-state migrants marooned too / Bhanupriya Rao -- Bihar's migrants return to face stigma, under-prepared medical facilities / Parul Agrawal -- Across India, workers complain that employers used lockdown to defraud them of wages they are owed / Rajiv Khandelwal -- India cannot fight a pandemic with police lathis. It must ensure people have food - and dignity / Supriya Sharma -- Differently-abled migrant women workers grapple with the pandemic / Vedika Kakar -- Pandemic crisis : 'migrant home-based women workers work 8 hours/day for Rs 10-15 / Cenny Thomas and Nivedita Jayaram -- Pandemic induced return of the migrant workers : response of West Bengal / Debashis Aich -- May day : 12-hour working day notifications / Jane Cox -- Changes in labour laws will turn the clock back by over a century / Ramapriya Gopalakrishnan -- Labour law changes : innocuous mistakes, sleight of hand or taking sides / Atul Sood and Paaritosh Nath -- Why Adityanath's simplistic migration commission is a non-starter / Juhie Singh -- Can labour reforms help women migrant workers during COVID-19? / Ellina Samantroy -- Media in the time of COVID-19 / Bhupen Singh -- How the Modi government manufactured public opinion during the migrant crisis / Aman Abhishek -- Not just the media, organised politics too failed India's migrant workers / Ranabir Samaddar -- Migrant crisis amid COVID is why we need 'journalism of misery' / Smruti Koppikar -- Lawyer Apar Gupta on what the Indian Supreme Court's order on COVID-19 coverage means for journalists / Kunal Majumder -- Audit of bigotry : how Indian media vilified Tablighi Jamaat over coronavirus outbreak / Ayan Sharma and Chahak Gupta -- Afterword: Were any lessons learnt? / Bharat Bhushan.
Includes bibliographical references and index.
Keywords: Migrant labor -- India -- Social conditions -- 21st century; Migrant labor in mass media; COVID-19 Pandemic, 2020- -- Social aspects -- India; COVID-19 Pandemic, 2020- , in mass media; Mass media -- Social aspects -- India; Labor policy -- India; Medical policy -- India; India -- Social conditions -- 21st century